Liposome-based multifunctional nanoplatform as effective therapeutics for the treatment of retinoblastoma - Ying Liu; Yu Han; Shizhu Chen; Jingjie Liu; Dajiang Wang; Yifei Huang (Elsevier, 2022)
Photothermal therapy has the characteristics of minimal invasiveness, controllability, high efficiency, and strong specificity, which can effectively make up for the toxic side effects and tumor resistance caused by traditional drug treatment. However, due to the limited tissue penetration of infrared light, it is difficult to promote and apply in clinical practice. The eye is the only transparent tissue in human, and infrared light can easily penetrate the eye tissue, so it is expected that photothermal therapy can be used to treat fundus diseases. Here in, a new nano-platform assembled by liposome and indocyanine green (ICG) was used to treat retinoblastoma. ICG was assembled in liposomes to overcome some problems of ICG itself. For example, ICG is easily quenched, self-aggregating and instability. Moreover, liposomes can prevent free ICG from being cleared through the systemic circulation. The construction of the nano-platform not only ensured the stability of ICG in vivo, but also realized imaging-guide photothermal therapy, which created a new strategy for the treatment of retinoblastoma.